Role of Shastika Shali Pinda Sweda in the Management of Pakshaghata (AYUSHDHARA, 2025)
Vata nanatmaja vyadhi pakshaghata is Mahavatavyadhi. It is caused due to vitiation of Vata which causes dryness of Sira and Snayu and manifest the features like loss of movement, pain and loss of speech. In Modern science it is correlated to hemiplegia. Hemiplegia is a neurological condition that leads to paralysis or weakness in the arm, leg, and sometimes the face on one side of the body. Swedana is the therapy that relieves the Stambha (stiffness of body), mitigates feeling of Guruta (heaviness of body) and Sheeta (feeling cold). The therapeutic treatment called “Shastika Shali pinda sweda” belongs to the category of Sagni Sweda therapies which use Snigdha (unctuous) Dravyas like milk and Shali dhanya (a type of rice). This treatment possesses Snigdha, Guru, Sthira, Sheeta, Tridoshagna and Brimhana guna. Localised thermal effect of Shastika Shali pinda sweda stimulate sweat glands to produce more heat. It accelerates the process by making the capillaries more permeable, allowing toxins to move into the extracellular fluid. It also dilates the capillaries causing increased blood flow and reduce inflammation optimize nerve conduction, enhancing sensory and motor functions. Pakshaghata, a condition often marked by impaired motor function and emotional disturbances, can be linked to imbalances in dopamine and serotonin. Shastika shali pinda sweda helps to rectify these imbalances by regulating neurotransmitter activity. In this article, attempt has been made to search mode of action of Shastika shali pinda sweda and its efficacy on Pakshaghata management according to need and condition.